PENGEMBANGAN PERANGKAT PEMBELAJARAN PBL BERMUATAN ETNOMATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN LITERASI MATEMATIKA PADA PESERTA DIDIK KELAS V SD - Puji Lestari; Ida Dwijayanti; Joko Siswanto (STKIP Subang, 2023)
The problem in this study is the lack of development of mathematics learning tools. The aim is to determine the validity, practicality, and effectiveness of PBL learning tools with ethno-mathematics content to improve mathematical literacy skills. This research is research and development with a design from Brog and Gall. The data collection instruments used were validity sheets for experts and practitioners, teacher and student response questionnaires, validation sheets for pretest and posttest mathematical literacy learning tools. The tools developed include RPP, Teaching Materials, Media, LKPD, Mathematical Literacy Questions. From the results of data analysis, the results of device validation were obtained as follows: lesson plans received a percentage value of 86.46% in the very valid category, 87.80 teaching materials were in the very valid category, 88.54% media were included in the very valid category, LKPD was 87, 50% is in the very valid category, test questions of 87.82% are in the very valid category. The practicality test was obtained from student and teacher questionnaires which were declared practical by students by obtaining an average score of 87.80 in the very good category and the practicality and readability response by the class teacher obtained a score of 87.5 in the very good category, and based on peer assessment it was obtained score of 86.25 is in very good category. The effectiveness test used is the paired sample t test and the gain n test. The test results of the sample t test get a sig value. 0.000, while the n gain test results get a value of 0.41 with the moderate increase category. The results showed that the Ethno-Mathematics PBL mathematics learning tool developed proved to be valid, practical and effective so that it is suitable for use in mathematics learning to improve students' mathematical literacy skills.